Comparative analysis of Al2O3-47 nm and Al2O3-36 nm hybrid nanoparticles in a symmetric porous peristaltic channel. (15th March 2021) - Khan, M Ijaz; Chu, Yu-Ming; Alzahrani, Faris; Hobiny, Aatef
Abstract: This study explores the flow of 47 nm and 36 nm size alumina-water nanoparticles in a symmetric porous peristaltic channel. Considered flow situation is modelled via magnetohydrodynamics (MHD), porous medium, linear radiation, dissipation due to viscosity, Joule heating and heat generation assumptions. Propagating channel walls contains the first order momentum and thermal slip aspects. Entropy is modelled using the thermodynamics second law. Here different effective viscosity models are introduced for 47 nm and 36 nm size alumina-water particles respectively. Lubrication theory is utilized here to simplify the dimensionless system. Numerical solution through built-in procedure is attained for coupled system of equation with respective boundary constraints. This numerical procedure gives the result of each flow quantity in the form of graphs for involved parameters. Further graphical results predicts that due to porous characteristics of walls secondary velocity decreases. Pressure gradient rises for higher magnetic parameter. All the plots of present analysis emphasized that 36 nm size alumina nanoparticles are more effective than the 47 nm size alumina nanoparticle.